Enamel microabrasion and dental bleaching on teeth presenting severe-pitted enamel fluorosis: A case report - Sundfeld, D.; Pavani, C. C. [UNESP]; Pini, N. I.P.; Machado, L. S.; Schott, T. C.; Sundfeld, R. H. [UNESP] (Operative Dentistry, 2019)
The present clinical case report describes the clinical steps of enamel microabrasion associated with dental bleaching to restore severely-pitted fluorosed teeth. The process of removing the fluorotic superficial stains started by using macroabrasion with a water-cooled fine tapered 3195 FF diamond bur. Rubber dam isolation of the operative field was used to remove the remaining enamel stains and superficial irregularities with the Opalustre microabrasive compound (6.6% hydrochloric acid associated with silicon carbide particles) followed by polishing using fluoridated paste and subsequent 2% neutral fluoride gel topical application. After one month, dental bleaching was performed using 10% carbamide peroxide in custom-formed acetate trays for two hours/day for 42 days. The association of enamel microabrasion with dental bleaching was effective for reestablishing the dental esthetics of a patient with severe dental fluorosis.